Peningkatan Kemampuan Sosial Emosional Anak Melalui Kegiatan Gotong Royong Disekolah - Maimunah, Umi; Sari, Henni Maya; Pebriani, Ela (CV. Utami, 2025)
The purpose of this study was to determine the improvement of children's social emotional abilities with gotong royong activities at TK Negeri 1 Suoh, Lampung Regency. This research is a Classroom Action Research (PTK) or also called Classroom action research with the procedures used in the form of cycles. The subjects of this study were group B children at TK Negeri 1 Suoh, Lampung Regency, totalling 22 children. The research was conducted in two cycles of two meetings. Data analysis was carried out in qualitative and quantitative descriptions with the emphasis used to determine the improvement of the process expressed in a predicate, while quantitative analysis was used to determine the improvement of results using percentages. The results of improving children's social-emotional abilities through gotong royong activities at State Kindergarten 1 Suoh in cycle I meeting to I with a percentage of 31.81%, in cycle I meeting to II with a percentage of 46.81%, cycle II meeting to I with a percentage of 57.27% and cycle II meeting to II with a percentage of 80.68%. The conclusion of the research is that using collage from dry leaf material can improve fine motor skills in children at TK Negeri 1 Souh, Lampung Regency, as evidenced in cycle II meeting II there was an increase with the results of the achievement percentage of 80.68% with very good developing criteria (BSB).